INCOMPATIBILITY ABO AND RH NEGATIVE BLOOD IN PREGNANT SERVED IN THE MILITARY HOSPITAL CENTRAL FOR A DECADE - Benavides Lozada, Benjamin (2015)
During the period of this study, in the HMC 77 g shelves they were treated in 118 pregnancies with blood group incompatibility and / or maternal-fetal Rh factor. - Resulting more often the first type Rh, ABO Combination () simultaneous ABO-RH (): Three types of inconsistency found.